FORSAKING EQUALITY: EXAMINE INDONESIA’S STATE RESPONSIBILITY ON POLYGAMY TO THE MARRIAGE RIGHTS IN CEDAW - N Nurhidayatuloh; F Febrian; Achmad Romsan; Annalisa Yahanan; Martinus Sardi; Fatimatuz Zuhro (Jurnal Dinamika Hukum, 2018)
Human rights violation (HRV) occurs when a state including its organs commits HRV to individual within its jurisdiction. International Law has formulated a wide range of human rights law, especially the CEDAW which has been ratified through Law No. 7 of 1984. However, the law has not been applied properly. This article aims to examine HRV committed by a state which caused inability or unwilling to amend polygamy Law. Based on normative research, analysis to Article 2(f) of the Convention applies a viewpoint equality and state responsibility theories. Through this method, international conventions will be opposed to national provisions, Polygamy regulation. It is found that Indonesia through Polygamy regulation performs discrimination against woman’s rights. It can be stated that Marriage Law treats men and women unequal. It concludes that, as a state, Indonesia should responsible for HRV because the main problem of inequality is discrimination rooted from Polygamy regulation.Keywords: equality, human rights violation, non-discrimination, polygamy, state responsibility